The Genome And Recombinant Capsid Protein Of A Newly Isolated Escherichia Phage Yd-2008.S - Sellvam, Dharmela (2018)
The numbers of discovered phages are just a minute fraction of its population in the biosphere. However, the advancement of genome sequencing technology as NGS (next generation sequencing) provides opportunity to identify more complete phage genomes data that feasible to register them in ICTV (International Committee on Taxonomy of Viruses). A tailed phage species designated as Escherichia phage YD-2008.s was discovered and the complete genome was sequenced and deposited in NCBI (National Centre for Biotechnology Information) database with GenBank accession No. KM896878.1.